Preclinical insights into fucoidan as a nutraceutical compound against perfluorooctanoic acid-associated obesity via targeting endoplasmic reticulum stress - Liu, Jiaqi; Guo, Chao; Wang, Yuqin; Su, Min; Huang, Wenjun; Lai, Keng Po (Frontiers in Nutrition, 2022)
Obesity is a growing global health problem, it is forecast that over half of the global population will be obese by 2030. Obesity is complicated with many diseases such as diabetes and cardiovascular diseases, leading to economic impact to the society. Other than diet, exposure to environmental pollutants is considered as a risk factor of obesity. Exposure to perfluorooctanoic acid (PFOA) was found to impair hepatic lipid metabolism, resulting in obesity. In this study, we applied network pharmacology and systematic bioinformatic analysis including gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes enrichment analysis (KEGG), together with molecular docking to investigate the targets of fucoidan for treating PFOA-associated obesity through the regulation of endoplasmic reticulum stress. Our results identified ten targets of fucoidan including GBA, GSR, MC4R, MMP2, MMP9, NFKB1, RELA, NR1I2, PPARD, and CRABP2. GO and KEGG enrichment analysis highlighted their involvement in the pathogenesis of obesity including lipid and fat metabolisms. More importantly, the gene cluster is responsible for the obesity-associated diseases and disorders such as insulin resistance, non-alcoholic fatty liver disease, and diabetic cardiomyopathy via the control of signaling pathways. The findings of this report provide evidence that fucoidan is a potential nutraceutical product against PFOA-associated obesity through the regulation of endoplasmic reticulum stress.